1995
DOI: 10.1021/j100045a034
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mo/C Catalysts by XRD, XPS, and TOF-SIMS

Abstract: A series of Mo/C catalysts were prepared by equilibrium adsorption of ( 4)6 7 24*4 20 onto a high surface area activated carbon. It was observed that the pH of the solution has a profound effect on the amount of Mo adsorbed on the carbon support. The Mo loading increases from ca. 0.2 to 14 wt % Mo as the pH of preparation decreases from 9 to 2. This behavior may be explained qualitatively in terms of electrostatic interactions between the molybdate ions and the protonated hydroxyl groups on the carbon surface.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Biochar from flash pyrolysis sorbed little SO 4 ‐S (Figure S2). Sulphate sorption to charcoal and gasification coke strongly increased at the two largest concentrations of CuSO 4 addition, most probably as a consequence of reduced pH values, as shown for molybdate sorption to activated carbon (Rondon et al , 1995; Figures S1 and S2). We therefore focused on SO 4 ‐S sorption observed for the five smallest CuSO 4 concentration ranges (Figure 2).…”
Section: Resultsmentioning
confidence: 75%
“…Biochar from flash pyrolysis sorbed little SO 4 ‐S (Figure S2). Sulphate sorption to charcoal and gasification coke strongly increased at the two largest concentrations of CuSO 4 addition, most probably as a consequence of reduced pH values, as shown for molybdate sorption to activated carbon (Rondon et al , 1995; Figures S1 and S2). We therefore focused on SO 4 ‐S sorption observed for the five smallest CuSO 4 concentration ranges (Figure 2).…”
Section: Resultsmentioning
confidence: 75%
“…It has been demonstrated that XPS can be used for monitoring the dispersion of metals as a function of metal loading on supported catalysts [5][6][7][8]. Those studies showed that information about dispersion obtained by using XPS can then be correlated with catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…The XPS metal-to-support intensity ratio will be proportional to the metal-to-support atomic ratio if the supported metal is dispersed as a monolayer. A thorough discussion of the model and some selected applications to supported catalysts are described elsewhere [5][6][7][8][9]. Some small modifications were made in the application of the K-M model for the calculation of the Pd/Al intensity ratios for monolayer coverage.…”
Section: Resultsmentioning
confidence: 99%
“…A series of Mo/C catalysts prepared with different Mo loadings (0.2±14 wt. %), and therefore at different pH values, were characterized by Rondon et al (1995). Fingerprints distinguished monomeric and polymeric Mo species.…”
Section: A Catalystsmentioning
confidence: 99%